1983
DOI: 10.2165/00003088-198308040-00002
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Food Intake on Presystemic Clearance of Drugs

Abstract: Many drugs have a low degree of oral bioavailability even though their gastrointestinal absorption is complete. This is because they undergo extensive presystemic metabolic transformation during the first passage of the drug through the gastrointestinal mucosa and the liver. In addition to effects on the absorption of some drugs, food intake has been found to influence the bioavailability of drugs with extensive presystemic metabolic clearance. Extensive presystemic clearance occurs commonly with compounds tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(46 citation statements)
references
References 44 publications
3
43
0
Order By: Relevance
“…Indeed, the mean peak plasma concentration (Cma) of verapamil if anything tended to be lower after food, 77 ng ml[,, in comparison with the fasting state, 118 ng ml-, P < 0.1 (Table 1). This is an unexpected observation since our standard meal contained 34 g protein, which in the study of Walle et al Melander & McLean (1983) have suggested that the food effect on bioavailability may only occur with drugs undergoing hydroxylation and conjugation since a standardised breakfast had no effect on the bioavailability of amitryptiline and prazosin where the presystemic metabolism involves dealkylation. The primary metabolic pathways of verapamil are N-dealkylation and O-demethylation (Eichelbaum et al, 1979) and thus our findings are consistent with this hypothesis.…”
mentioning
confidence: 79%
“…Indeed, the mean peak plasma concentration (Cma) of verapamil if anything tended to be lower after food, 77 ng ml[,, in comparison with the fasting state, 118 ng ml-, P < 0.1 (Table 1). This is an unexpected observation since our standard meal contained 34 g protein, which in the study of Walle et al Melander & McLean (1983) have suggested that the food effect on bioavailability may only occur with drugs undergoing hydroxylation and conjugation since a standardised breakfast had no effect on the bioavailability of amitryptiline and prazosin where the presystemic metabolism involves dealkylation. The primary metabolic pathways of verapamil are N-dealkylation and O-demethylation (Eichelbaum et al, 1979) and thus our findings are consistent with this hypothesis.…”
mentioning
confidence: 79%
“…Nifedipine undergoes first pass metabolism with a bioavailability in the region of 40-70% (Waller et al, 1984). Food has been shown to influence the pre-systemic clearance of some drugs such as propranolol and prasozin (Melander & McLean, 1983 that the extent of nifedipine absorption was influenced by food and it therefore seemed unlikely that such mechanisms were operating in the case of nifedipine.…”
Section: Discussionmentioning
confidence: 99%
“…Superficially, observations related to food and hydralazine suggest that flow-mediated mechan- (McLean et al, 1978) regardless of the model which applied. Similarly, effects of shunt processes over similar time frames would tend to be obscured by delayed absorption of drug (Melander & McLean, 1983). The processes underlying the interaction remain unexplained even though long-term metabolic inhibition appears to be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…The processes underlying the interaction remain unexplained even though long-term metabolic inhibition appears to be excluded. A variety of mechanisms are possible, including short-term inhibition of enzymes, short-term changes in flow, or redistribution of flow with non-homogenous distribution of enzymes (Melander & McLean, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation